Gender and food from production to consumption and after. - Segal, Marcia Texler, 1940-; Demos, Vasilikie P. (Advances in gender research, 2016)
Volume 22 explores the complex relationships between gender and food in a variety of locations and time periods using a range of research methods. Authors show that gender inequality and mens dominance are implicit or explicit, and that in times of both stability and change, the burden of many if not most aspects of food production and provisioning falls upon women and is an integral part of the care work they perform. Food is shown to be related to societal structures of power, resources and labor markets, as well as households, bodies and emotions. Health, well-being and sustainability emerge as major tropes in the economic and geographic north and south from the arctic to the equator and places between. Western cultural trends regarding specialized diets as they relate to health and illness are examined from a gender lens as is childrens nutrition worldwide. Gender inequality as it affects the struggle for access to land, the affordability of food, and its nutritional value is identified as a major social policy issue.